Reducing the incidence of phlebitis in medical adult inpatients with peripheral venous catheter care bundle: a best practice implementation project. Issue 1 (28th March 2021) - Gunasundram, Sumathi; Tan, Mary; Lim, Koon Z.H.; Loh, Veronica M.P.
Abstract : Supplemental Digital Content is available in the text ABSTRACT: Background: One major complication of the insertion of a peripheral venous catheter (PVC) is phlebitis, often resulting in delay of treatment, increased healthcare costs and prolonged hospitalization. Aims: The current study sought to evaluate the effectiveness of a standardized PVC care bundle in increasing the compliance of PVC care and assessment and reduce the occurrences of phlebitis rates. Methods: A pre and postimplementation audit approach was used in this study and adopted the Joanna Briggs Institute Practical Application of Clinical Evidence System and Getting Research into Practice program. This study was carried out in three phases over a 10-month period, from March 2017 to December 2017 across three medical wards in a hospital in Singapore with a sample size of 90 patients. The study involved educating nurses on phlebitis assessment, implementing a PVC care bundle and monitoring compliance. An audit tool comprising four criteria from the Joanna Briggs Institute Practical Application of Clinical Evidence System was developed. Results: One-month and 3-month postimplementation findings revealed significant improvement in Criteria 1, 3 and 4 ( P < 0.001) but no significant improvement in Criterion 2 ( P > 0.05). Six-month postimplementation findings showed significant improvement in all four criteria ( P < 0.05). An interesting finding was that the number of reported occurrences of phlebitis increased after implementing the PVC care bundle. Discussion: The increase in phlebitis rates could be attributed to the care bundle facilitating prompt and early identification of phlebitis. Despite the initial increase in occurrences 1 month post implementation, the general effectiveness of the care bundle in reducing occurrences of phlebitis was seen 6 months post implementation. The effectiveness of the care bundle to reduce phlebitis rates may be even more evident across a longer implementation period. Conclusion: The current study showed that the implementation of a standardized PVC care bundle can significantly enhance the assessment and identification process of phlebitis and can aid in reducing the incidence of phlebitis. The nurses' compliance in practicing the PVC care bundle was determined by the post and preimplementation audits, thus, the audit approach was beneficial in translating evidence into practice.